2020
DOI: 10.1088/1361-6471/abaeb1
|View full text |Cite
|
Sign up to set email alerts
|

Role of residual interaction in the relativistic description of M1 excitation

Abstract: Magnetic dipole (M1) excitation is the leading mode of multi-nucleon excitations induced by the magnetic field, and is a phenomenon of the spin–orbit splitting and residual interactions involved. In this work, we investigate the effects of the residual interactions on the M1 excitation from a novel perspective, the framework of relativistic nuclear energy-density functional. The relativistic Hartree–Bogoliubov model is utilized to determine the nuclear ground state properties, while the relativistic quasi-part… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
37
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 17 publications
(41 citation statements)
references
References 68 publications
4
37
0
Order By: Relevance
“…In further studies of open shell nuclei, it is shown that pairing correlations have a significant impact on the centroid energy and major peak position of the M1 mode [21,22]. From the analysis of M1 mode in the Ca isotope chain, the role of the isovector-pseudovector (IV-PV) residual interaction has been discussed [22].…”
Section: Magnetic Dipole Transitions In the Relativistic Quasiparticle Random Phase Approximationmentioning
confidence: 99%
See 2 more Smart Citations
“…In further studies of open shell nuclei, it is shown that pairing correlations have a significant impact on the centroid energy and major peak position of the M1 mode [21,22]. From the analysis of M1 mode in the Ca isotope chain, the role of the isovector-pseudovector (IV-PV) residual interaction has been discussed [22].…”
Section: Magnetic Dipole Transitions In the Relativistic Quasiparticle Random Phase Approximationmentioning
confidence: 99%
“…In further studies of open shell nuclei, it is shown that pairing correlations have a significant impact on the centroid energy and major peak position of the M1 mode [21,22]. From the analysis of M1 mode in the Ca isotope chain, the role of the isovector-pseudovector (IV-PV) residual interaction has been discussed [22]. It has been shown that the experimental data on M1 mode could improve and optimize the theoretical aspects to describe the residual interactions in the RQRPA.…”
Section: Magnetic Dipole Transitions In the Relativistic Quasiparticle Random Phase Approximationmentioning
confidence: 99%
See 1 more Smart Citation
“…[2,3,[7][8][9][10]. For example, in studies based on the Skyrme energy-density functional (EDF) [11][12][13][14][15] as well as on the relativistic EDF [16,17], the interplay between the SO splittings and the residual interactions has been investigated. In addition, the M1 transition is sensitive to the pairing correlations in open-shell nuclei [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…For example, in studies based on the Skyrme energy-density functional (EDF) [11][12][13][14][15] as well as on the relativistic EDF [16,17], the interplay between the SO splittings and the residual interactions has been investigated. In addition, the M1 transition is sensitive to the pairing correlations in open-shell nuclei [17,18]. Note that, although the concept of M1 transition originates in the electo-magnetic interaction, this transition can be invoked also by strong-interaction probes [9,[19][20][21].…”
Section: Introductionmentioning
confidence: 99%